Environmental flow assessment of high gradient river system using integrated habitat simulation method - Hasan, Hasrul Hazman (2017)
River system has a paramount role to support various ecological functions apart from its crucial importance as the main water resource for man-related activities. Despite of its countless benefits to various river developments and uses, the integrity of the river shall never be compromised to ensure the resource sustainability and balanced ecosystem. The increase in multisector’s water demand has lead to various river-uses issues with no exception of conservation and economic development perspective. The environmental flow assessment serves as a crucial first step in determining the alteration level that a river can withstand before it gets malfunctioned. This study adopted the combined methods of the hydrologic index, hydraulic rating and habitat simulation method for the environmental flow assessment of a high gradient tropical river system in Mid Perak State of Malaysia, namely Pelus River. There were two main objectives of the study; i) to correlate the by-seasons flow regimes and river physical habitat characteristics for Habitat Suitability Curve (HSC) development of the bioindicator species (Barbodes binotatus), and ii) to propose the river physical habitat and river flow tolerance range for different river management options and implications. Apart from the 30 years hydro-climatic secondary data, three sets of primary data representing normal, dry and wet seasons have been used as the main data source to increase the accuracy of the final result. The standard procedure of data sampling and processing were applied in accordance to established procedures including APHA and DID Malaysia guideline. Three HSCs of the Barbodes binotatus have been successfully constructed for depth, velocity and substrate parameter, which suggesting different Area Weighted Suitability (AWS) of the bioindicator species. Different sets of river management options and its implication have been proposed by fully-utilise the information of the tolerance range of specific flow and physical habitat characteristics to satisfy the different level of environment flow requirement. The environmental flow for a river system should be able to meet the agreed objective of the river uses set forth, and the implication must be well understood by the river stakeholders before a project can be conducted.